1999
DOI: 10.1016/s0002-9270(99)00204-x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus infection of the colon with inflammatory bowel disease

Abstract: The limited presence of EBV-infected cells in the diseased areas of IBD colonic specimens indicated that EBV infection may be related to such diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 22 publications
6
48
1
Order By: Relevance
“…Cho et al [24] reported the same result that EBV was not associated with colorectal tumors. However, Yanai et al [23] found that EBV was detected in 63.6 % of Crohn's disease cases and 60 % of ulcerative colitis cases using in situ hybridization for EBV-encoded small RNA1 (EBER-1), indicating that EBV infection may be related to IBD colonic diseases. Ioachim et al [26] studied 15 cases of primary anorectal lymphoma in AIDS patients and compared them with 4 cases of anorectal lymphoma unrelated to AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al [24] reported the same result that EBV was not associated with colorectal tumors. However, Yanai et al [23] found that EBV was detected in 63.6 % of Crohn's disease cases and 60 % of ulcerative colitis cases using in situ hybridization for EBV-encoded small RNA1 (EBER-1), indicating that EBV infection may be related to IBD colonic diseases. Ioachim et al [26] studied 15 cases of primary anorectal lymphoma in AIDS patients and compared them with 4 cases of anorectal lymphoma unrelated to AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in a potential etiopathogenic role of Virus de Epstein-Barr (VEB) in IBD arose when an increased number of B lymphocytes infected with VEB was found in mucosal samples from UC colons, and, to a lesser degree, in CD samples [98] . Epidemiological data indicate that frequency of infection is similar in IBD patients and healthy controls, both approximately 100% [99] .…”
Section: Virus De Epstein-barrmentioning
confidence: 99%
“…Patients with inflammatory bowel disease (IBD), such as Crohn's disease and ulcerative colitis (UC), display increased numbers of EBV-infected lymphocytes in their inflammatory mucosae (14,15). Immunosuppressive therapy in IBD patients can reactivate latent EBV infections, which can lead to enteropathy (16).…”
Section: Discussionmentioning
confidence: 99%